Fluid–structure coupled simulation of ignition transient in a dual pulse motor using overset grid method. (June 2021) - Li, Yingkun; Chen, Xiong; Cheng, Honggang; Zhao, Zemin
Abstract: In this paper, the second pulse ignition transient in a dual pulse solid rocket motor with elastomeric barrier pulse separation device has been conducted numerically. An in-house code has been developed to solve governing equations for unsteady compressible flow, heat conduction and structural dynamic. The solid propellant ignition and burning numerical models have been added. The fluid structure interaction is implemented by using the conventional serial staggered algorithm. The large deformation and expansion of the elastomeric barrier are addressed by the dynamic overset grid technology. The accuracy of the numerical method is validated by the experimental cases. Then, the detailed flow field development, pressure evolution, flame propagation characteristics in the combustion chamber, and the structural response of elastomeric barrier are analyzed carefully. The rupture-time and rupture-pressure of the elastomeric barrier are also obtained. The numerical results show that the elastomeric barrier deformation presents a small displacement at the front part and a large displacement at the rear section. The interaction of the compression waves and expansion waves from the convergent portion of the nozzle and from the motor head-end, as well as the supersonic annular jet flow in the combustion chamber, can induce obvious pressure rises with fluctuations and spikes. The first pulse free volume has a significant effect on the time to reach a steady state. Highlights: The ignition transient in a DPSRM with elastomeric barrier was simulated using a multi-physics coupling method. The large deformation and expansion of elastomeric barrier was addressed by overset grid technology. The flame propagation characteristics and structural response of elastomeric barrier were analyzed.